Pengaruh Disiplin Kerja, Loyalitas dan Kompensasi Terhadap Kinerja Perangkat Desa di Kecamatan Manna Kabupaten Bengkulu Selatan - Gayatrie Ratna Bella; Ahmad Soleh; Tito Irwanto (UNIVED Press, 2023)
The purpose of this study was to determine the effect of work discipline, loyalty and compensation on the performance of village officials in Manna District, South Bengkulu Regency. The regression results show Y = 17.770 + 0.281X1 + 0.219X2 + 0.125X3 These results describe a positive regression direction, meaning that there is a positive influence between X1 (Work discipline), X2 (loyalty), X3 (Compensation), on performance (Y). This means that if the variables of work discipline, loyalty and compensation increase, the performance of village officials will increase. The magnitude of the Coefficient of Determination is 0.130. This means that X1 (work discipline), X2 (loyalty) and X3 (compensation) affect performance (Y) by 13% while the remaining 87% is influenced by other variables not examined in this study. The results of the t test at a significant level of 0.05 explain that partially (individually) the variables of work discipline, loyalty and compensation have a significant influence on the performance variables of village officials because the significant value is less than 0.05. The results of the F test at a significant level of 0.05 explain that the variables of work discipline, loyalty and compensation have a simultaneous (together) influence on the performance of village officials because the significant value is less than 0.05.